C-Met targeting in advanced gastric cancer: An open challenge. Issue 1 (28th August 2015) - Marano, Luigi; Chiari, Rita; Fabozzi, Alessio; De Vita, Ferdinando; Boccardi, Virginia; Roviello, Giandomenico; Petrioli, Roberto; Marrelli, Daniele; Roviello, Franco; Patriti, Alberto
Highlights: Different compounds targeting c-Met have been developed and tested in gastric cancer. Discouraging outcomes of anti-c-Met monoclonal antibodies has been recently underlined. No clear anti-tumor activity was identified in small molecule c-Met inhibitors except for high c-Met-positive tumors. Several biomarkers are being explored in order to clarify the question of potential treatment benefits in selected patients. Abstract: Despite significant improvements in systemic chemotherapy over the last two decades, the prognosis of patients with advanced gastric and gastroesophageal junction adenocarcinoma (GC) remains poor. Because of molecular heterogeneity, it is essential to classify tumors based on the underlying oncogenic pathways and to develop targeted therapies acting on individual tumors. High-quality research and advances in technology have contributed to the elucidation of molecular pathways underlying disease progression and have stimulated many clinical studies testing target therapies in an advanced disease setting. In particular, strong preclinical evidence for the aberrant activation of the HGF/c-Met signaling pathways in GC cancers exists. This review will cover the c-Met pathway, the mechanisms of c-Met activation and the different strategies of its inhibition. Next, we will focus on the current state of the art in the clinical evaluation of c-Met-targeted therapies and the description of ongoing randomized trials with the idea that in this disease, high quality translational research to identify and validate biomarkers is a priority task.